2017
DOI: 10.1097/ta.0000000000001649
|View full text |Cite
|
Sign up to set email alerts
|

The role of splenic angioembolization as an adjunct to nonoperative management of blunt splenic injuries: A systematic review and meta-analysis

Abstract: Systematic review and meta-analysis, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 61 publications
(114 reference statements)
0
51
0
2
Order By: Relevance
“…In the more recent case study of mitral valve replacement for IE by Shafi et al, 25 with hemodynamic stability and moderate to severe splenic injury. [2][3][4][5][6][7][10][11][12] While the use of SAE in atraumatic splenic rupture is supported by a growing number of case studiesincluding the rare case of post-operative splenic rupture post cardiac surgery for IE -, 25 the role of SAE in atraumatic injury has not specifically been defined. [17][18][19][20][21][22][23][24] Further research is needed to understand which conditions resulting in splenic rupture may be best suited for treatment with embolization, as well as when to intervene in these cases, what criteria to base intervention on and which embolization technique may be of most benefit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the more recent case study of mitral valve replacement for IE by Shafi et al, 25 with hemodynamic stability and moderate to severe splenic injury. [2][3][4][5][6][7][10][11][12] While the use of SAE in atraumatic splenic rupture is supported by a growing number of case studiesincluding the rare case of post-operative splenic rupture post cardiac surgery for IE -, 25 the role of SAE in atraumatic injury has not specifically been defined. [17][18][19][20][21][22][23][24] Further research is needed to understand which conditions resulting in splenic rupture may be best suited for treatment with embolization, as well as when to intervene in these cases, what criteria to base intervention on and which embolization technique may be of most benefit.…”
mentioning
confidence: 99%
“…Over the last few decades there has been a shift to non‐operative management with the goal of splenic salvage. While opinions do still vary, it is general consensus in the interventional radiology and surgical literature, that hemodynamically unstable patients with splenic injury should be treated with operative management while those who are hemodynamically stable will benefit most from non‐operative management (NOM) strategies 2‐7 …”
mentioning
confidence: 99%
“…In 2013, Cirocchi et al performed a systematic review and concluded that they could not clarify the safety and efficacy of NOM for severe splenic trauma because of the selection bias and heterogeneity of the studies [ 3 ]. In 2017, Crichton and his colleagues compared the effectiveness of AE as an adjunct to NOM with that of NOM alone in all grade BSI and concluded that AE significantly improves the success of NOM of AAST grade IV and V BSIs [ 4 ]. As seen above, once NOM was selected for high-grade BSI, AE should be performed, although safety of NOM for high-grade BSI is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Some trauma centers may have a hybrid operating room with an integrated angiographic suite (54). A recent meta-analysis of hemodynamically stable patients with splenic injury showed no overall difference between nonsurgical treatment success with or without splenic angioembolization, but patients with grade IV or V injuries had significantly fewer instances in which nonsurgical treatment was unsuccessful when splenic angioembolization was performed (11,55). To our knowledge, persistent mesenteric hemorrhage after DCS has not been reported in the literature but can be encountered (Fig 16, Movie 6).…”
Section: Ongoing Hemorrhagementioning
confidence: 99%